(untitled) (ModaPalavra e-periódico, 2022)
In the face of the Russian Revolution of 1917, the result of which proposed a new economic model that until then had never been put into practice, revolutionaries found themselves in the need to create a new reality that would not only change the laws and the economy, it would also change the lives of the population in its most basic sense. The so-called Novy Byt was a theoretical formulation of how daily life should be under socialism, and for the construction of this new way of life, it was necessary to educate the population in the ideals of the revolution, ideals that were absorbed by the constructivist artistic avant-garde, who in the following years dedicated himself to creating objects that would change the way the population consumes. The present article is dedicated to the visual study of the prints created by Liubov Popova and Varvara Stepanova between 1923 and 1924, who sought in a graphic way to educate the population in revolutionary ideals.